Bacterial cellulose-poly(acrylic acid-co-N, N′-methylene-bis-acrylamide) interpenetrated networks for the controlled release of fertilizers. Issue 32 (15th May 2018) - Zaharia, Anamaria; Radu, Anita-Laura; Iancu, Stela; Florea, Ana-Mihaela; Sandu, Teodor; Minca, Iulian; Fruth-Oprisan, Victor; Teodorescu, Mircea; Sarbu, Andrei; Iordache, Tanta-Verona
Abstract : In this study, composite hydrogels with interpenetrated polymer networks (IPNs), based on bacterial cellulose (BC) and poly(acrylic acid- co-N, N ′-methylene-bis-acrylamide) (PAA) were synthesized by radical polymerization. Abstract : In this study, composite hydrogels with interpenetrated polymer networks (IPNs), based on bacterial cellulose (BC) and poly(acrylic acid- co-N, N ′-methylene-bis-acrylamide) (PAA), were synthesized by radical polymerization and characterized herein for the first time. Liquid fertilizer (LF) formulations, containing potassium, phosphorus, ammonium oxides and micronutrients, were encapsulated directly into the IPNs of the composite hydrogels during synthesis. Thermal analyses and scanning electron microscopy of control and composite xerogels highlighted the formation of IPNs between BC and PAA. Swelling determinations confirmed the influence of the crosslinker and of the liquid fertilizer concentration upon the density of the IPNs. Further rheology studies and release profiles indicated how the presence of BC and the increase of the crosslinking density of IPNs improved the mechanical strength and the release profile of LF for the innovative composite BC-PAA hydrogels. Results regarding the fertilizer release indicated that the presence of the BC led to a more controlled liberation of the fertilizer proving that this new formulation is potentially viable for application in agricultural practices.